Digital Marketing as a Media of Developing and Marketing Electric Motorbike Products as a Result of Training Assisted by the Department of Industry and Trade - Ni Putu Natasya Amelia Putri; Ida Nyoman Basmantra (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Marketing is an essential key for a company to increase sales of the products produced by the company. With the rapid progress of science and technology, everything has modernized, especially in marketing a product. Currently, companies can sell their products by doing digital marketing. With digital marketing, companies can do marketing through the help of the internet, such as social media. With social media, product marketing can be done without limits and at any time, reaching a broader range of customers. Training under the guidance of the Denpasar City Department of Industry and Trade produced a product for converting conventional motorbikes into electric motorbikes in collaboration with SMEs. Meanwhile, product marketing could have been more optimal due to the lack of product marketing. One of the right strategies for marketing is marketing through digital media or digital marketing. Besides, it needs to aid and train for training participants in SMEs. Digital marketing as a means for the development and marketing of electric motorcycle products resulting from training assisted by the Department of Industry and Trade, especially for SMEs. Finally, it is based on marketing products through social media with content or trends that contain electric motors.